Preparing the students for today’s careers / Nor Alwani Omar and Ezzah Suraya Sarudin - Omar, Nor Alwani; Sarudin, Ezzah Suraya (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2020)
Faculty of Computer and Mathematical Science, in collaboration with Mathematical Sciences Club (PERSIK) had organized a programme called Advanced Excel Programme: A Step to Mar-ketable Graduates on October 12, 2019 at Smart Classroom, UiTM Perak Branch, Tapah Campus. This programme was organized for the semester 4 and 5 students as part of the preparation for the future career prospect.